Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
See Explanation
Step-by-step explanation:
Given
Base Dimension
[tex]Length = 4\frac{1}{4}yd[/tex]
[tex]Width = 1\frac{2}{3}yd[/tex]
Required
The base area of all containers
First, calculate the base area of 1 container.
This is calculated as:
[tex]Area = Length * Width[/tex]
[tex]Area = 4\frac{1}{4}yd * 1\frac{2}{3}yd[/tex]
Express as improper fraction
[tex]Area = \frac{17}{4}yd * \frac{5}{3}yd[/tex]
So, we have:
[tex]Area = \frac{17*5}{4*3}yd^2[/tex]
[tex]Area = \frac{85}{12}yd^2[/tex]
The number of containers is not given. So, I will use 'n' as the number of containers.
So, we have:
[tex]Total = n * Area[/tex]
[tex]Total= n * \frac{85}{12}yd^2[/tex]
--------------------------------------------------------------------------------------------
Assume n is 3 (i.e. 3 containers)
The total area is:
[tex]Total= 3 * \frac{85}{12}yd^2[/tex]
[tex]Total= \frac{85}{4}yd^2[/tex]
[tex]Total= 21\frac{1}{4}yd^2[/tex]
--------------------------------------------------------------------------------------------
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.